Integrating Solar Cells, Arduino, and Sensors for Vocational Science Education: A Scoping Review - M. Raynaldo Sandita Powa (SEAMEO QITEP in Science, 2026)
Vocational science learning requires contextual, hands-on experiences that reflect real-world technological applications. Solar cell systems integrated with Arduino and various sensors represent low-cost technological platforms with strong potential to be adapted as learning media for renewable energy topics in vocational education. Numerous studies have developed solar-Arduino-sensor systems for monitoring, tracking, acquiring data, and experimenting in a laboratory; however, these developments have not been systematically mapped from an educational perspective. This study employed a scoping review to map the landscape of existing research on solar cell–Arduino–sensor system designs. The initial literature research was conducted using Publish or Perish (PoP) based on Google Scholar indexing, followed by iterative searching and reference tracking during the review process. A total of 20 articles published between 2015 and 2025 were selected for data charting and thematic analysis. The results revealed several major clusters of system development, including solar tracking mechanisms, sensor-based photovoltaic monitoring, Internet of Things (IoT) architectures, portable photovoltaic laboratory instruments, and immersive solar education technologies. Although most studies were conducted in engineering and monitoring contexts, the identified designs demonstrated strong potential to be adapted as contextual science learning media aligned with the characteristics of vocational education. This mapping provides a comprehensive overview of technological designs that can support the development of vocational science learning tools based on solar cells, Arduino, and sensor integration.